Clinical efficacy of nebivolol and metoprolol in complex treatment of patients with coronary heart disease and II-III functional class chronic heart failure - A. G. Evdokimova; A. E. Radzevich; O. I. Tereshchenko; E. V. Kovalenko (Кардиоваскулярная терапия и профилактика)
Aim. To investigate clinical efficacy of nebivolol and metoprolol in the complex treatment of patients with coronary heart disease (CHD) and II-III functional class chronic heart failure (CHF). Material and methods. The study involved 110 patients with CHD and CHF, functional class II-III, by NYHA classification. All participants, aged 47-79 years, had ejection fraction <45%. The patients were divided into three groups. Group I (n=38) received nebivolol (2.5-5 mg/d) plus standard therapy; Group II (n=36) – metoprolol tartrate (50-100 mg/d) plus standard therapy; Group III (n=36) – only standard therapy. During 4-month followup, the following parameters were assessed: clinical efficacy, physical stress tolerance (PST), quality of life (QoL), number and duration of silent myocardial ischemia episodes (SMIE), left ventricular (LV) structural, functional and hemodynamic parameters, blood rheology, platelet aggregation, and lipid profile. Results. At baseline, no significant decrease of LV total contractility was observed. Four month later, in all treatment groups PST increased, number and duration of SMIE reduced, patients’ condition, central hemodynamics and LV remodeling parameters improved, as well as lipid profile, blood rheology and platelet hemostasis. Positive dynamics was greater in nebivolol group. Conclusion. In complex treatment of patients with CHD and CHF, nebivolol acts similar to metoprolol. Nebivolol increased treatment efficacy, increased PST, reduced number and duration of SMIE, prevented LVH progression, improved clinical status, QoL, lipid profile, platelet hemostasis, blood rheology.